Техногенное загрязнение почв тяжелыми металлами в регионе разработки газовых месторождений Сургиль (SCIENCE and SOCIETY, 2025)
The article is dedicated to the study of soil contamination with heavy metals in the Surgil gas fields of the dried-up bottom of the Aral Sea. Analysis was carried out using the gradient indication method and Le Chatelier’s criterion. Accumulation of Pb, Cd, Ni, Zn, and Cu has been identified, especially in the northern and northeastern directions. The